The Effect of Sexual Activity on Wages - Nick Drydakis (Institute for the Study of Labor (IZA), 2013)
The purpose of this study is to estimate whether sexual activity is associated with wages, and also to estimate potential interactions between individuals' characteristics, wages and sexual activity. The central hypothesis behind this research is that sexual activity, like health indicators and mental well-being, may be thought of as part of an individual's set of productive traits that affect wages. Using two stage estimations we examine the relationship between adult sexual activity and wages. We estimate that there is a monotonic relationship between the frequency of sexual activity and wage returns, whilst the returns to sexual activity are higher for those between 26 and 50 years of age. In addition, heterosexuals' sexual activity does not seem to provide higher or lower wage returns than that of homosexuals, but wages are higher for those health-impaired employees who are sexually active. Over-identification tests, robustness checks, falsification tests, as well as, decomposition analysis and sample selection modelling enhance the study's strength. Contemporary social analysis suggests that health, cognitive and non-cognitive skills and personality are important factors that affect the wage level. Sexual activity may also be of interest to social scientists, since sexual activity is considered to be a barometer for health, quality of life, well-being and happiness. The paper adds to the literature on the importance of unobserved characteristics in determining labour market outcomes.
Keywords: J10; J30; J24; 330; sexual activity; wages; endogeneity; sample selection; decompositions